Memetic Perspectives on the Evolution of Tonal Systems in Music. (June 2015) - Jan, Steven
<x content-type="archive" xml:space="preserve">Abstract</x> Cohn (1996) and Taruskin (1985) consider the increasing prominence during the nineteenth century of harmonic progressions derived from the hexatonic and octatonic pitch collections respectively. This development is clearly evident in music of the third quarter of the century onwards and is a consequence of forces towards non-diatonic organization latent in earlier music. This article conceptualizes such forces as memetic — drawing a distinction between memetic processes in music itself and those in the realm of music theory — and interprets the gradualistic evolution of tonal systems as one of their most significant consequences. After outlining hypotheses for the mechanisms driving such evolution, it identifies a number of 'musemes' implicated in hexatonic and octatonic organization in a passage from Mahler's Symphony no. 10. Pople's (2002) Tonalities music-analysis software is used to explore the tonal organization of the passage, which is considered in relation to the musemes hypothesized to generate and underpin it.